Daya Hambat Ekstrak Kulit Buah Kakao (Theobroma Cacao L.) terhadap Pertumbuhan Bakteri Staphylococcus Aureus Rosenbach dan Escherichia Coli Migula - Aulia Nurbaiti; A. A. Ketut Darmadi; Sang Ketut Sudirga (Pusat Riset dan Inovasi Nasional, 2025)
Cocoa fruit peel (Theobroma cacao L.) is an agricultural waste with potential as an antibacterial agent due to its bioactive compounds. Pathogenic bacterial infections, such as Staphylococcus aureus and Escherichia coli, pose significant health problems, particularly due to the increasing resistance of bacteria to antibiotics. This creates a demand for alternative, safer, and more effective antibiotics. This study aims to evaluate the effectiveness of cocoa fruit peel extract in inhibiting the growth of S. aureus and E. coli, determine the Minimum Inhibitory Concentration (MIC), and identify the bioactive compound groups contained in the extract. The methods used in this study include maceration for the extraction of cocoa fruit peel, the well diffusion method to test the antibacterial activity of the crude extract, and phytochemical testing to identify the bioactive compounds in the extract. The results show that the crude extract of cocoa fruit peel can inhibit the growth of S. aureus with an inhibition zone diameter of 26.75 mm and E. coli with an inhibition zone diameter of 25.75 mm. The MIC test revealed that S. aureus was more sensitive to the extract, with an MIC at a concentration of 0.7%, resulting in an inhibition zone diameter of 5.35 mm, while E. coli showed an MIC at a concentration of 0.8%, with an inhibition zone diameter of 5.36 mm. The most effective concentration was 50%, with inhibition zone diameters of 20.56 mm against S. aureus and 21.06 mm against E. coli. Phytochemical testing showed that the cocoa fruit peel extract contains alkaloid, tannin, saponin, triterpenoid, and flavonoid compounds. Based on the results, cocoa fruit peel extract demonstrates potential as an effective natural antibacterial agent against S. aureus and E. coli.